(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nyctanthes arbor-tristis extract Belongs to dicot family could be a little sacred decorative tree. This plant has several healthful properties. Totally different components are used historically for treatment of varied diseases like neuralgia, chronic fever, antidiabitic, antioxidant and antibacterial activity etc. For extraction of plant both Hot (Chloroform and Methanol) and cold (Petroleum Ether) extractions method were performed by using different solvent. The plant based mostly knowledge has become a recognized tool in explore for new sources of drugs. Standard procedures were used to take a look at the presence of assorted phytochemicals. Tannins, saponins, flavonoids and phenol all were found during this plant. The present study finished that this therapeutic valuable plant have possessed different important phytochemicals that helps within the therapeutic properties of the studied plants normally utilized in different disease.